Optimization Unloading Time Container Use Multiple-Channel Queuing Model at Car Industry - Fitra, Adi; Suhendra, Suhendra; Wiyatno, Tri Ngudi (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
The development of the car assembly industry in Indonesia is increasing from year to year and competition is getting tighter. To be able to compete in the competition, a system with low costs is needed. Logistics is an activity that does not add value and logistics is also included in the price formation elements. Logistics costs in Indonesia are high, reaching 30% of the total product. Waiting time for containers to be unloaded is a hidden cost and can reduce service levels. The aim of this research is to reduce waste when waiting to unload containers which is related to the capacity of the area waiting to unload containers. The method used is the Multiple-Channel Queuing Model queuing method where analysis is carried out to reduce waiting time so that there are no containers waiting outside the cross-dock warehouse. The results of the research found that by increasing the number of containers unloading docks, the unloading time could be reduced from 2.25 hours to 1 hour and increase the service level where the container waiting area which initially required 5 parking lots became 2 container parking lots. Not only can it reduce the number of queues outside the warehouse and reduce waiting times. In this study, it was found that by adding docking from 2 to 3, it can make a cost reduction of 1 million per month because there is no need to pay overtime costs to unload containers.